Odpowiedzi

2009-12-28T23:14:29+01:00
Wykonaj dzialania i zapisz wyrazenia w najprostszej postaci.
^2 - oznacza do potęgi drugiej

a) 3x(kwadrat)-(5-2x-3xkwadrat)-x(2x-3)=
3x^2 - (5 -2x -3x^2 ) -x(2x-3)=
= 3x^2 - 5 +2x +3x^2 -2x^2+3x=
= 4x^2 + 5x -5

b)(4a-2b)kwadrat
(4a-2b)^2 =
= 16a^2 - 16ab + 4b^2

c)(5x+2)kwadrat-(x-2)(x+2)
= (5x+2)^2 - ( x^2 - 4)=
= 25x^2 + 20x +4 -x^2 +4=
= 24x^2 +20x +4

d)(4-3a)szescian
(4-3a)^3=
Stosuje wzór: (a-b)^3 = a^3 -3a^2*b+ 3b^2*a - b^3
=64 - 3*16*3a + 3*9a^2 - 27a^3=
= 64 - 144a + 27a^2 -27a^3

e)(x-5)kwadrat-(2x+7)kwadrat
= (x -5)^2 - (2x+7)^2=
= x^2 -10x +25 -(4x^2 + 28x + 49)=
= x^2 -10x +25 - 4x^2 - 28x - 49 =
= -3x^2 -38x -24


f)2(3-4a)kwadrat-(a+2)(a-1)
= 2(3-4a)^2 -(a^2 -a +2a -2)=
= 2(9 -24a + 16a^2) -(a^2 +a -2)=
= 18 - 48a +32a^2 -a^2 -a +2=
= 31a^2 - 49a +20